PHYSICO-CHEMICAL PROPERTIES AND ENERGY POTENTIAL OF WOOD WASTES FROM SAWMILLS IN BENIN METROPOLIS, NIGERIA (Nigerian Journal of Technology, 2017)
The physico-chemical properties and energy potential of wood wastes were evaluated in this study. Wood wastes from five tropical species: Ekki (Lophira alata); Ohia (Celtis sp); Danta (Nesogordonia papaverifera); Omah (Cordia millenii) and Black Afara (Terminalia ivorensis) collected from sawmills across Benin Metropolis, the capital of Edo State, in South Western Nigeria were used as feedstock. Calorific values, moisture contents as well as proximate and ultimate analyses were performed to assess the energy characteristics of the collected wood wastes in accordance with the American Society for Testing and Materials: ASTM E872-82 and ASTM D4442-07. Results from the laboratory experiments and energy calculations revealed that the wood wastes used in this study contain relatively low moisture and ash contents, high proportions of volatile matter and carbon, high calorific values, low levels of sulphur and nitrogen as well as a sufficiently high value of thermal energy potential. The results are indications that the wood wastes are suitable as feedstock for renewable energy generation with little or no threat to the environment.http://dx.doi.org/10.4314/njt.v36i2.18